2023
DOI: 10.5093/ejpalc2023a3
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Emotional Symptoms and their Relationship with Different Types of Cybervictimization

Abstract: Background: Cyberbullying is a highly prevalent problem in our society with important implications for adolescent psychological wellbeing. The objective of the study was to examine the network structure of the Depression, Anxiety, and Stress Scale in a sample of youths, and find out the relationships between different types of cybervictimization and the presence of negative emotional states. Method: This was a descriptive cross-sectional study. The sample was made up of 2,171 high school students with a mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
(49 reference statements)
1
10
0
1
Order By: Relevance
“…The data reflect that girl victims have greater emotional manifestations of stress, compared to boy victims who have more behavioral manifestations, physical activity, and self-esteem. As stated by Molero et al [ 33 ], girls have higher mean scores in stress, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The data reflect that girl victims have greater emotional manifestations of stress, compared to boy victims who have more behavioral manifestations, physical activity, and self-esteem. As stated by Molero et al [ 33 ], girls have higher mean scores in stress, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 80%
“…Peer victimization can negatively affect young people’s life satisfaction, decreasing their perception of community support and impairing their development and quality of life [ 32 ]. In addition, positive correlations have been found between cybervictimization and levels of anxiety, depression, and stress, with adolescent girls having higher means [ 33 ]. Young people who lead a healthy lifestyle based on good hygiene, physical activity, and abstinence from tobacco have a lower probability of being bullied or being victims of school violence [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrariwise, other reviews [ 55 , 56 ] attribute the effectiveness in reducing recidivism to the improvement in psychopaths of the strategies to avoid legal detention as a consequence of the skills acquired in treatment. In any way, psychopathic traits have an indirect effect on emotional intelligence, a critical skill for an effective treatment of psychopathy [ 57 ] and the palliation of the emotional clinical symptoms and, by extension, a mitigation of recidivism [ 58 ]. Fourth, a superficial, grandiose, and manipulative personality (interpersonal traits) as well as callousness and lack of remorse (affective traits) define CPOs in comparison to non-CPOs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that dysfunctional family environments have a direct impact on adolescent development with detrimental consequences in both the short and long term, which is why it has been proposed to preserve the social and psychological well-being of adolescents by addressing the relationship between adequate development and family cohesion [6][7][8]. In addition to these findings, several authors demonstrate the importance of a well-functioning family for this stage that favours a greater state of psychological wellbeing and increases emotional skills in adolescents so that they can develop positively [9,10] and improve their cognitive performance [11].…”
Section: Introductionmentioning
confidence: 99%